A practical guide to structured expert elicitation using the IDEA protocol. Issue 1 (5th September 2017) - Hemming, Victoria; Burgman, Mark A.; Hanea, Anca M.; McBride, Marissa F.; Wintle, Bonnie C.
Abstract: Expert judgement informs a variety of important applications in conservation and natural resource management, including threatened species management, environmental impact assessment and structured decision‐making. However, expert judgements can be prone to contextual biases. Structured elicitation protocols mitigate these biases, and improve the accuracy and transparency of the resulting judgements. Despite this, the elicitation of expert judgement within conservation and natural resource management remains largely informal. We suggest this may be attributed to financial and practical constraints, which are not addressed by many existing structured elicitation protocols. In this paper, we advocate that structured elicitation protocols must be adopted when expert judgements are used to inform science. In order to motivate a wider adoption of structured elicitation protocols, we outline the IDEA protocol. The protocol improves the accuracy of expert judgements and includes several key steps which may be familiar to many conservation researchers, such as the four‐step elicitation, and a modified Delphi procedure ("Investigate, " "Discuss, " "Estimate" and "Aggregate"). It can also incorporate remote elicitation, making structured expert judgement accessible on a modest budget. The IDEA protocol has recently been outlined in the scientific literature; however, a detailed description has been missing. This paper fills that important gap by clearly outlining each of the steps required to prepare for and undertake an elicitation. While this paper focuses on the need for the IDEA protocol within conservation and natural resource management, the protocol (and the advice contained in this paper) is applicable to a broad range of scientific domains, as evidenced by its application to biosecurity, engineering and political forecasting. By clearly outlining the IDEA protocol, we hope that structured protocols will be more widely understood and adopted, resulting in improved judgements and increased transparency when expert judgement is required.